Respuesta :

Answer:

Answer: Fourth option [tex]10x^{4}\sqrt{6}+x^{3}\sqrt{30x} -10x^{4}\sqrt{3}-x^{3}\sqrt{15x}[/tex]

Step-by-step explanation:

First we open the bracket and then simplify the products in the given question.

Now we start the question.

⇒[tex]2\sqrt{10x^{4}(15x^{4})}-2x\sqrt{5x^{2}(15x^{4})} +\sqrt{10x^{4}(3x^{3}) } -x\sqrt{5x^{2}(3x^{3})}[/tex]

⇒[tex]2\sqrt{150x^{8} }-2x\sqrt{75x^{6} }+\sqrt{30x^{7} } -x\sqrt{15x^{5} }[/tex]

⇒[tex]2x^{4}\sqrt{150}-2x^{4} \sqrt{75}+x^{3}\sqrt{30x} -x^{3}\sqrt{15x}[/tex]

⇒[tex]2(x^{4})5\sqrt{6}-2(x^{4})5\sqrt{3}+x^{3}\sqrt{30x} -x^{3}\sqrt{15x}[/tex]

⇒[tex]10x^{4}\sqrt{6}+x^{3}\sqrt{30x} -10x^{4}\sqrt{3}-x^{3}\sqrt{15x}[/tex]